2020
DOI: 10.1021/acs.jpclett.0c01772
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Photoconductivity and Long-Lived Charge Carriers in Bismuth-Based One-Dimensional Perovskite with Type-IIa Band Alignment

Abstract: Bismuth-based perovskites are attracting intense scientific interest due to low toxicity and excellent moisture stability compared to lead-based analogues. However, high exciton binding energy, poor charge carrier separation, and transport efficiencies lower their optoelectronic performances. To address these issues, we have integrated an electronically active organic cation, naphthalimide ethylammonium, between the [BiI 52− ] n chains via crystal engineering to form a novel perovskite-like material (naphthali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 44 publications
(56 reference statements)
0
31
0
Order By: Relevance
“…Nevertheless, the way of the organic semiconductor molecules in manipulating the charge transport within the OIHPs lattice remains controversial. When there is a definite π-stacking between the conjugated organic ligands, the carrier migration (n- or p-type) may be partially contributed from the embedded organic semiconductors. , Moreover, highly ordered and efficiently π-stacked organic semiconductors is clarified to be necessary for the generation of long-lived charge carriers for 1D perovskites . If there is no direct π–π interaction between the adjacent organic ligands, the organic layer must not be the conductive channel that is responsible for the high charge carrier mobilities .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the way of the organic semiconductor molecules in manipulating the charge transport within the OIHPs lattice remains controversial. When there is a definite π-stacking between the conjugated organic ligands, the carrier migration (n- or p-type) may be partially contributed from the embedded organic semiconductors. , Moreover, highly ordered and efficiently π-stacked organic semiconductors is clarified to be necessary for the generation of long-lived charge carriers for 1D perovskites . If there is no direct π–π interaction between the adjacent organic ligands, the organic layer must not be the conductive channel that is responsible for the high charge carrier mobilities .…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Moreover, highly ordered and efficiently π-stacked organic semiconductors is clarified to be necessary for the generation of long-lived charge carriers for 1D perovskites. 22 If there is no direct π−π interaction between the adjacent organic ligands, the organic layer must not be the conductive channel that is responsible for the high charge carrier mobilities. 11 In this case, the changes in lattice bonding features within the inorganic layers including lattice contraction and shortened average cationic nitrogen to peripheraliodide (N−I) distance dictated by the conjugated organic cations may be the origin of the high carrier mobilities.…”
Section: Introductionmentioning
confidence: 99%
“…Akin to the lead halide hybrid perovskites, large alkyl cations were then adopted to design bismuth halide perovskite for obtaining better humidity stability. [15][16][17][18] For instance, Nair et al designed and fabricated a (1,3-propanediammonium) 2 Bi 2 I 10 •2H 2 O film, and demonstrated a parallel configured photodetector with a responsivity of 1.14 mA W −1 and repeatable photocurrent in several light on/off cycles. 15 Besides, Zheng et al reported a novel (TMP) 1.5 [Bi 2 I 7 Cl 2 ] perovskite, and achieved obvious photoconductivity and high moisture and light stability.…”
Section: Introductionmentioning
confidence: 99%
“…A wider choice of organic cations [7], which no longer have to meet strict size requirements [8,9], allows obtaining 2D- [10], 1D- [11,12] or 0D- [13] hybrid perovskites with promising optoelectronic properties. To further improve their performance in solar cells [14], inert organic cations are sometimes replaced [15] by electroactive molecules [16][17][18][19][20], including those encountered in organic charge-transfer complexes [18,[21][22][23][24]. The latter may potentially provide additional functionalities to hybrid perovskites [25], such as (super)conductivity, photoconductivity, ferroelectricity and magnetoresistance [26,27] useful for optoelectronic devices [28].…”
Section: Introductionmentioning
confidence: 99%